The Development of student worksheets based on a scientific approach in the dynamic fluid concepts. Issue 1 (May 2021) - Halim, A; Ulandari, S; Hamid, A; Wahyuni, A; Syukri, M; Irwandi, I
Abstract: This study aims to develop student worksheets (SW) based on the Scientific Approach on the concept of dynamic fluids. Another objective is to determine the level of validity and response of students. The design of this study uses the R&D (Research and Development) method with the ADDIE model including the stages of analysis, design, development, implementation and evaluation. This research was conducted at the Public Middle School, Prisai Kutacane district, Southeast Aceh in class XI IPA 1, which numbered 36 people. The data collected comes from validity tests by experts, reliability, pilot tests and student responses. The data collection instruments that used were tests, questionnaires and observation sheets. The results showed that the SW validity level tested by experts was in the very good category. Based on the results of this study, it can be concluded that by applying the SW-based scientific approach, learning the dynamic fluid concept becomes more effective.